Influence of Olea europea L. and Ficus Carrica L. fine root activity on the K biodisponibility and clay mineralogy of the rhizosphere - Sophia Mouas-Bourbia; Pierre Barre; Malika Boudiaf-Nait Kaci; Malika Mouffok; Mohamed Rebbouh; Lila Kessouri; Hallima Ouahab; Arezki Derridj; Bruce Velde (Eurasian Journal of Soil Science, 2015)
The objective of this study was to compare the effect of fine root activity of Olea europea L. and Ficus carrica L. of soil in its immediate vicinity (in the so-called rhizosphere zone). The study was conducted on two stations in Northern Algeria: Guendoul and Bouira. Olea europea L. and Ficus carrica L. roots significantly modified some chemical properties of rhizosphere soil. Increases of soil carbon, KNH4+ and KHNO3- were observed in the Olea europea L. and Ficus carrica L rhizosphere soil at both stations. Bulk and rhizosphere soil clay mineralogy was similar. Interstratified illite-smectite, smectite-illite and illite were predominant in the clay fraction. Chlorite and kaolinite were less represented. The decomposition of XRD diffractograms of two soil clay fractions using the Decomp program revealed that Olea europea L. roots promote nK+ storage in interlayer position. Indeed, the lower abscissa position of the gravity center (cg) of the X-ray patterns, the peak displacement of clays populations PCI, I/S, S/I toward illite peak position indicates an increase of “illite-like” layer content in the vicinity of Olea europea L. roots. Olea europea L. roots appeared to have more influence on the rhizosphere soil than Ficus carrica L. roots probably because of its higher root biomass and the greater activity of the tree in winter (contrary to Ficus Carrica L., Olea europea L. keep their leaves in winter). The two species underground activity seems to be well reflected in their respective rhizosphere.